Factor Analysis of E-learning Readiness of Undergraduate Students in Faculty of Education Ramkhamhaeng University - Panidvadtana, Panida (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
The purpose of this research was to analyze factors of E-learning readiness of students in Faculty of Education Ramkhamhaeng University. The sample was 1,067 undergraduate students. The research instrument was E-learning readiness instrument with the Index of Item-Objective Congruence being 1.00 and the reliability of the whole questionnaire being 0.814. The analysis of E-learning readiness components used exploratory factor analysis (EFA) with the method of principal component analysis and direct oblimin. The research findings were as follows: The E-learning readiness components of the students in Faculty of Education Ramkhamhaeng University had six components. The components consisted of 1. self-efficacy, 2. access of opportunity, 3. adjustment, 4. concentration, 5. sense of comfort, and 6. self-management. All of these 6 components could be explanatory of variance at 53.671 percent.